2005
DOI: 10.1038/sj.cgt.7700891
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cell death in human papillomavirus 18-positive cervical cancer cells by E6 siRNA

Abstract: Human cervical cancer is caused by high-risk types of human papillomavirus (HPV) such as HPV16 and HPV18, which possess the E6 and E7 oncogenes, whose concurrent expression is a prerequisite for cancer development and maintaining malignant phenotypes. Silencing these oncogenes is considered to be applicable in molecular therapies of human cervical cancer. However, it remains to be determined whether E6, E7, or both should be silenced to obtain most efficient antitumor activity by an HPV smallinterfering RNA (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 38 publications
3
35
0
1
Order By: Relevance
“…These results encourage further investigation of RNAi as a potential treatment for cervical cancer. Although the knockdown of HPV E6 and E7 expression in HeLa cells has been reported by a few groups using siRNA, 14,13,18 we showed here a stable knockdown of E6 or E7 in HeLa cells (at least 2 weeks) with LV-shRNA. In previous reports, Yoshinouchi et al 17 showed that synthetic HPV 16 siRNA induced a modest reduction in tumor growth of SiHa cells in NOD/ SCID mice.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…These results encourage further investigation of RNAi as a potential treatment for cervical cancer. Although the knockdown of HPV E6 and E7 expression in HeLa cells has been reported by a few groups using siRNA, 14,13,18 we showed here a stable knockdown of E6 or E7 in HeLa cells (at least 2 weeks) with LV-shRNA. In previous reports, Yoshinouchi et al 17 showed that synthetic HPV 16 siRNA induced a modest reduction in tumor growth of SiHa cells in NOD/ SCID mice.…”
Section: Discussionmentioning
confidence: 76%
“…[8][9][10][11][12] Previous studies have demonstrated that small interference RNA (siRNA) can suppress HPV E6 and/or E7 expression in various cancer cell lines. [13][14][15][16][17][18] However, the suppression in these studies was either transient (owing to the short half-life of siRNA), against only one target, or not all cells were transfected leading to escape. We wished to improve these results by using shRNA delivered by a third-generation lentiviral vector for a more effective, stable and long-term RNAi.…”
Section: Introductionmentioning
confidence: 97%
“…Among the promising gene approaches developed thus far to specifically target E6 and/or E7 (5), it was found that siRNA led to ablation of E6 in HPV18-positive HeLa cells leading to apoptosis, albeit under harsh conditions of cell transfection (7,10). Studies done with siE6 or short hairpin RNA showed that treated HeLa or SiHa cells did not die but stopped proliferating and became more sensitive to chemotherapy (9,22,32).…”
Section: Discussionmentioning
confidence: 99%
“…5B). Inhibiting E6/E7 gene transcription in HPV-transformed cells using small interfering RNA has similarly been shown to reduce cell growth and/or induce apoptosis in HPV-transformed cells (40,41).…”
Section: Why Might This Two-step Process For Rb Degradation Havementioning
confidence: 99%